The Role of Memorization Intensity in Qur'anic Memorization Ability: A Correlational Study - Astuti, Sri Hartini Juni; Nurhayati, Nurhayati; Pahrurraji, Pahrurraji; Echwan, Chairul; Setiawan, Bagus; Nuruddaroini, M. Ahim Sulthan (LP. Ma'arif Janggan Magetan, 2024)
This research is motivated by the low ability to memorize the Qur'an of some tahfizh students, even though they have participated in an intensive memorization program. This indicates a gap between the memorization process and achievement, which encourages the need to identify factors that influence memorization ability. This study aims to analyze the influence of memorization intensity and psychological well-being on students' ability to memorize the Qur'an. This study uses a quantitative method with a survey approach. The number of respondents is 110 people. The data obtained are analyzed quantitatively using multiple linear regression analysis. The results show that (1) memorization intensity has a significant effect on the ability to memorize the Qur'an (p = 0.007; β = 6.5), (2) psychological well-being does not have a significant effect (p = 0.417; β = 00.5), and (3) simultaneously, both variables only explain 7% of the variation in memorization ability, while 93% is influenced by other factors. This study highlights the dominant role of memorization intensity in enhancing Qur'anic memorization and offers new insights into how internal psychological factors interact in the context of higher education tahfizh programs. The novelty of this study lies in its integrated analysis of memorization intensity and psychological well-being in a single model, contributing to a deeper understanding of the psychological factors that influence Qur'anic memorization.